On thermal analysis, macrostructure and microstructure of grain refined Al–Si–Mg cast alloys: role of Sr addition. (October 2014) - Golbahar, B.; Samuel, E.; Samuel, A. M.; Doty, H. W.; Samuel, F. H.
<x content-type="archive" xml:space="preserve">Abstract</x> The present study aimed at investigating the influence of grain refinement in combination with Sr modification on the solidification behaviour of A356·2 alloy, and the resulting micro- and macrostructures obtained. Grain refinement of A356·2 alloy using Ti and B additions in the ranges of 0·02–0·5% and 0·01–0·5% respectively was studied using five different grain refiners in the form of Al–10%Ti, Al–5%Ti–1%B, Al–2·5%Ti–2·5%B, Al–1·7%Ti–1·4%%B and Al–4%B aluminium master alloys. Sr modification of the alloys was carried out using Sr additions of 30 and 200 ppm in the form of Al–10%Sr master alloy. The probable interactions between Sr and Ti and Sr and B were investigated using different metallographic techniques. Thermal analysis was also used to evaluate these interactions. Electron microprobe analysis revealed that adding >0·1%B to the A356·2 alloy may lead to formation of particles predominantly containing B and Sr, with a composition approaching SrB6.